2016
DOI: 10.1364/oe.24.026152
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field sensing using standard uniform FBGs

Abstract: Magnetic field sensing can be directly (i.e. without requiring magnetic fuilds or magnetostrictive materials) obtained from the estimation of the circular birefringence induced in optical fibers through the so-called Faraday effect. In standard telecommunication-grade optical fiber, the amount of induced circular birefringence is however of the same order of the intrinsic fiber linear birefringence or even below. Hence, whenever uniform fiber Bragg gratings (FBGs) are used to probe this evolution, the resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The magnetic field strength can be obtained by computing the diattenuation vector. It is a new demodulation technique allowing the use of a FBG written in common single-mode fiber (SMF) [21]. Amirsolaimani et al developed a high sensitivity magnetometer using nanocomposite polymers, as shown in Figure 2.…”
Section: Magnetic Field Optical Sensorsmentioning
confidence: 99%
“…The magnetic field strength can be obtained by computing the diattenuation vector. It is a new demodulation technique allowing the use of a FBG written in common single-mode fiber (SMF) [21]. Amirsolaimani et al developed a high sensitivity magnetometer using nanocomposite polymers, as shown in Figure 2.…”
Section: Magnetic Field Optical Sensorsmentioning
confidence: 99%
“…As opposed to examining Mueller matrix coefficients as previously done [8], we take the fundamental properties of the fibre such as polarization dependent loss (PDL) and polarisation mode dispersion (PMD), analysing the results to determine a correlation to the induced magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…While FBGs are widely used in different sensing applications, the photo-inscription process that causes the refractive index modulation also causes an increase in the region of one order of magnitude in linear fibre birefringence. This obscures the induced birefringence and has previously required complex data processing, preventing real time monitoring [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation